TEC-mediated tRF-31R9J regulates histone lactylation and acetylation by HDAC1 to suppress hepatocyte ferroptosis and improve non-alcoholic steatohepatitis - Juanjuan Zhu; Xian Wu; Mao Mu; Quan Zhang; Xueke Zhao (Clinical Epigenetics)
Abstract Background Tectorigenin (TEC) is a monomer of anthocyanin, which we found exhibits hepatoprotective effects. tRNA-derived fragments (tRFs) and ferroptosis play important roles in the pathogenesis of non-alcoholic steatohepatitis (NASH). Recent discoveries have revealed that histone lactylation and acetylation play a crucial role in connecting cellular metabolism and epigenetic regulation through post-translational modification of histones. However, it is unclear whether TEC improves NASH by regulating histone lactylation, acetylation and hepatocyte ferroptosis through tRFs. Results In this study, we demonstrated that TEC significantly inhibits free fatty acids-induced hepatocyte ferroptosis both in vitro and in vivo. We identified tRF-31R9J (tRF-31-R9JP9P9NH5HYD) involved in TEC regulation of ferroptosis in steatosis hepatocytes. Overexpression of tRF-31R9J suppressed hepatocyte ferroptosis and enhanced cell viability in steatosis HepG2 cells. Knockdown of tRF-31R9J partially counteracted the inhibitory effect of TEC on ferroptosis in hepatocytes. Mechanistically, tRF-31R9J recruited HDAC1 to reduce the levels of histone lactylation and acetylation modifications of the pro-ferroptosis genes ATF3, ATF4, and CHAC1, thereby inhibiting their gene expression. Conclusions This study demonstrates that TEC-mediated tRF-31R9J inhibits hepatocyte ferroptosis through HDAC1-regulated histone delactylation and deacetylation, thereby improving NASH. These discoveries offer a theoretical foundation and new strategies for the medical management of NASH.